MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN KRITERIA KETUNTASAN MINIMAL MELALUI METODE PENDAMPINGAN DI SD NEGERI BOJONGKERTA KOTA BOGOR - Neneng Sumiati (Journal of Social Studies, Arts and Humanities (JSSAH), 2022)
IMPROVING TEACHER COMPETENCE IN DEVELOPING MINIMUM COMPLETENESS CRITERIA THROUGH ASSISTANCE METHODS AT BOJONGKERTA ELEMENTARY SCHOOL, BOGOR CITYThe purpose of this study was to improve the teacher's ability to develop minimum completeness criteria through mentoring for elementary school teachers in Bojongkerta, South Bogor District, Bogor City. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and Reflection. Based on the results of action research that Mentoring can Improve Teachers' Ability in Developing Minimum Completeness Criteria for Teachers at SDN Bojongkerta, South Bogor District, Bogor City. Furthermore, the researcher recommends: (1) Principals who have the same difficulty can apply Mentoring to improve the ability to develop Minimum Completeness Criteria for Guided Teachers. (2) In order to obtain maximum results, intensive and sustainable individual assistance can be applied. This research can provide benefits, especially: (1) For teachers, an effective method can be found in compiling minimum criteria for completeness, (2) for school principals to increase their role as supervisors so that they can improve teacher abilities, (3) for schools to determine the direction of learning achievement in learning. one school year.